Metode Eklektik dalam Pembelajaran Bahasa Arab - Siti Milatul Mardiyah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2020)
Learning methodology is very necessary in the learning process. The success of a learning process also depends on the methodology, especially in learning Arabic. Many kinds of methods can be applied in teaching and learning activities, for example: lecture method, qawa'id wa al tarjamah method, preacher method, and so forth. Although there are many kinds of learning methods in learning Arabic, unfortunately there are still advantages and disadvantages of those methods. As a result of these events, the eclectic method was born, which is a combined method/mixture of methods that already existed before. This method has a goal to be achieved, namely the purpose of several methods chosen and combined, so that language skills can be collected all in this method and teaching and learning activities can run efficiently and optimally. In language learning, there is no perfect method used for various learning purposes, because the methods that can be used still have advantages and disadvantages. However, these methods can be used properly and correctly according to the needs in the learning process, so that learning objectives can be achieved. The use of methods in the learning process is adjusted to the needs of a teacher in delivering information / material to his students. So, the Arabic learning methods are chosen and used as needed, and they are not used as a whole.